Intergenerational Shifting of Profanity Words among Multilingual Generations: Millennial and Gen-Z - Triastama Wiraatmaja; Kharisma Naidi Warnanda Sabgini (Soegijapranata Catholic University, 2026)
Social media over the years lately had shaped the language shifting or code mixing in global contexts. This qualitative research aimed to unravel the intergenerational language shifting in profanity usage between millennials and generation-Z; the corpus about profanity words uttered by both, reasons for the usage of profanity words, and how this research perceived the intergenerational shifting of profanity words under the paradigm of sociolinguistics point of view. This research deployed open-ended surveys as primary instrument to gather profanity words used by both generations, including their reasonings for using them. Participants were selected through purposive sampling to ensure relevant representations from two different generations. The respondents consisted of 20 Gen-Z English-major students from various universities, and 9 Millennial English lecturers. They were recruited using institutional networks and online survey distribution. This technique was required because it assisted the researchers to target participants with related linguistics contexts and generational characteristics. The results indicated that gen-Z favorite profanity words in social media usage in recent years were cok or jancok, and it was due to the socio-cultural reasons behind it. Contrastively, the millennials stated that the socio-cultural and linguistics were the reasons regarding their favored word which was fuck. Through document analysis, the researchers perceived that Gen-Z’s shifting preferences for profanity words were driven by the social-cultural interaction , and FOMO (fear of missing out) as they seek peer acceptance and a heightened sense of belongings. In contrast, the millennials preferences were primarily to express their sense of group solidarity without concerns about social exclusion or ostracism. Although Gen-Z uttered profanity words to express themselves, the researchers highlighted that both generations feared feeling of remorse and potential consequences of using such language. Therefore, the researchers perceived that intergenerational shifting of profanity reflected a complex phenomenon that encompassed sociolinguistics and psycholinguistics frameworks